2003
DOI: 10.1177/0022487103259114
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Enacting Caring Teacher Education

Abstract: To prepare teachers who will be able to draw on caring to build a strong foundation for their professional practices, teacher education programs must be created specifically focused toward this goal. This article discusses the use of dialogue journals in a course designed to enrich preservice elementary teachers’ understandings of caring. Quite unexpectedly, the dialogue journals demonstrated some of the preservice teachers developing negative, judgmental, and adversarial attitudes toward the parents of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…Definitions of ‘caring teachers’ in this literature draw heavily upon Noddings () concept of an ethic of care, which emphasises the importance of understanding the needs of those being cared for and acting in accordance to those needs. Although it has been critiqued from a feminist perspective for perpetuating exploitation of caregivers (Hoagland, ), and through a Foucauldian lens for justifying further extraction of uncompensated moral and ethical labour from teachers (McCuaig, ), Western teacher education emphasises cultivation of this ethic of care (Goldstein & Freedman, ; Rogers & Webb, ). Research also demonstrates a connection between caring teachers and positive student outcomes (J. L. Lewis et al, ; Mihalas et al, ; C. Muller, ; Riconscente, ).…”
Section: Introductionmentioning
confidence: 99%
“…Definitions of ‘caring teachers’ in this literature draw heavily upon Noddings () concept of an ethic of care, which emphasises the importance of understanding the needs of those being cared for and acting in accordance to those needs. Although it has been critiqued from a feminist perspective for perpetuating exploitation of caregivers (Hoagland, ), and through a Foucauldian lens for justifying further extraction of uncompensated moral and ethical labour from teachers (McCuaig, ), Western teacher education emphasises cultivation of this ethic of care (Goldstein & Freedman, ; Rogers & Webb, ). Research also demonstrates a connection between caring teachers and positive student outcomes (J. L. Lewis et al, ; Mihalas et al, ; C. Muller, ; Riconscente, ).…”
Section: Introductionmentioning
confidence: 99%
“…This giving and receiving of care equates to the relationship that can develop as teachers connect, person-to-person, with students. Goldstein and Freedman (2003) studied preservice teachers and their beliefs about caring and the nature of the interactions between the teachers and learners. They found that preservice teachers are learning to teach by watching their teachers (teacher educators).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Caring in unique contexts-Technologymediated Goldstein & Freedman, 2003 Examines the use of e-journals in a pre-service teacher course. Raises questions relevant to caring pedagogy in online education.…”
Section: Bruce and Stellern 2005mentioning
confidence: 99%
“…The Caring Study (Rogers & Webb, 1991) reported ethnographic data from eight classrooms that suggested curriculum construction, modeling, dialogue, reflection, confirmation, practice and continuity are essential in teacher preparation programs. Goldstein and Freedman (2003) took a more practical approach by collecting data using electronic dialogue journals in a teacher preparation course while explicitly teaching about and with an ethic of care. From this, Goldstein developed the Cornerstones of Caring model, which included a commitment to an ethic of care, passion for learning and intimacy-in-community.…”
Section: Developing Caring Characteristicsmentioning
confidence: 99%